2020
DOI: 10.1016/j.ijcha.2020.100675
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of infective endocarditis during the coronavirus disease 2019 pandemic: A nationwide study

Abstract: Highlights The incidence of IE during lockdown was 11.1 IE cases per 100,000 PY. No reduction in the incidence of IE during the lockdown compared to preceding years. No difference in the incidence of IE pre- versus post-lockdown in 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
5
0
4
Order By: Relevance
“… 39 A Danish nationwide study of infective endocarditis (IE) hospitalizations found no difference during the pandemic, whereas a Mexican single-centre study showed a 93% reduction. 40 , 41 One single-centre study reported a decline in hospitalizations with adult congenital heart disease (ACHD) during the pandemic, 42 and two studies demonstrated a significant increase in the incidence of stress cardiomyopathy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“… 39 A Danish nationwide study of infective endocarditis (IE) hospitalizations found no difference during the pandemic, whereas a Mexican single-centre study showed a 93% reduction. 40 , 41 One single-centre study reported a decline in hospitalizations with adult congenital heart disease (ACHD) during the pandemic, 42 and two studies demonstrated a significant increase in the incidence of stress cardiomyopathy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…В целом, пока не выявлено нарастания частоты ИЭ в период пандемии COVID-19 [33]. Однако в этих условиях диагностика ИЭ затягивается ввиду необходимости дифференциальной диагностики с COVID-19 и обусловленных этим сложностей с госпитализацией [34].…”
Section: Discussionunclassified
“…These contributing factors could ultimately lead to the development of IE. However, it should be noted that researchers from Denmark reported no significant difference in overall IE incidence during the first six months of the 2020 COVID-19 pandemic [26]. The association between COVID-19, IE, and opioid use remains an unanswered question.…”
Section: Covid-19 and Iementioning
confidence: 99%